Dari Hafalan Hadis ke Aksi Ekologis: Integrasi Nilai Islam dalam Pengelolaan Sampah untuk Meningkatkan Kesadaran Lingkungan Siswa MA Ma’arif Gembong - Fuad Khakim; Dian Tias Aorta (Lembaga Yasin AlSys, 2026)
Although environmental education based on Islamic values has received attention in several previous studies, research that specifically discusses the integration of hadith memorization in waste management to improve students’ environmental awareness remains limited. This study aims to analyze the integration of Islamic values through hadith memorization in waste management and its impact on students’ environmental awareness at MA Ma’arif Gembong. This study used a qualitative approach with a descriptive design, involving students, teachers, and related parties selected through purposive sampling. Data were collected through observation, interviews, and documentation and were then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation. The results showed that the integration of Islamic values through hadith memorization had a positive impact on character formation and increased students’ awareness of environmental cleanliness. Hadith memorization activities accompanied by understanding of meaning and direct practice, such as sorting and disposing of waste in the proper place, were effective in instilling the values of cleanliness, responsibility, and environmental care. This program was implemented in a structured manner through memorization activities, discussions, practice, evaluation, and communal cleaning activities, thereby encouraging increased student discipline in maintaining the cleanliness of the school environment. However, its implementation still faced obstacles in the form of low initial student awareness, limited facilities, and a lack of program consistency. The conclusion of this study affirms that habituating Islamic values through practical activities plays an important role in shaping environmentally caring behavior. These findings provide a theoretical contribution to the development of character-based Islamic education and practical implications for schools in designing integrative, applicable, and sustainable environmental learning strategies.